Recent Development in Synthesis of Carbon Dots from Natural Resources and Their Applications in Biomedicine and Multi‐Sensing Platform. Issue 11 (18th March 2021) - Bag, Puja; Maurya, Rahul K.; Dadwal, Ankita; Sarkar, Mrinmoy; Chawla, Pooja A.; Narang, Raj K.; Kumar, Bhupinder
Abstract: Carbon has always found a spotlight in human life either in the form of graphite, diamonds, activated charcoal, carbon nanotubes, or carbon dots (CDs). Carbon quantum dots (CQDs) or CDs became the centre of attraction because of their potential applications in biomedical field such as bio‐imaging, drug nanocarriers, gene therapeutics, photosensitizing agents, theranostics and provides other multifunctional diagnostic platforms. There are numerous advantages of CDs due to their biocompatibility, reduced toxicity, water‐solubility, ease of scale‐up, and, most notably their fluorescence properties contrary to other carbon nanostructures. In last few years, significant efforts have been put by various research teams to synthesize and develop nanostructured materials possessing specific functional properties and characteristics. This work focus on the recent developments in the synthetic approaches applied for CDs using environment‐friendly sources. This review also highlights the mechanistic aspects, applications of CDs in biomedicine and a multi‐sensing platform along with challenges and future perspectives of this promising field. The authors believe that this review will help audible researchers to select a suitable environment‐friendly approach for the synthesis of CDs from green sources with required functions and properties. It will also guide researchers to develop a more convenient, efficient, and environment‐friendly method for the synthesis of new tunable carbon dots. Abstract : In the current review, we have compiled various synthetic methodologies employed in synthesis of carbon dots from various natural resources. Biocompatibility, reduced toxicity, water‐solubility, ease of scale‐up, and, most notably its fluorescence properties are contrary to other carbon nanostructures. Along with synthetic strategies, we have also compiled various bioimaging and multi‐sensing applications of these carbon dots.